Filmes cintiladores baseados em oxissulfeto de gadolínio - Thiago de Lourenco e Vasconcelos (2011)
In this work, Gd2O2S based scintillators thick films were prepared using sedimentation and mechanical compression methods. The films produced were characterized using SEM and optical microscope. The light yield of each film was measured in a setup similar to the x-ray imaging system. In this system, x-ray is converted in light by a scintillator film. The light is converged into a CMOS sensor. A comparison between the experimental data and a simple theoretical model was performed. As a result, some modifications of the film preparation method and structural parameters were described. Using the optimized parameters for the scintillator film, enhanced light yield is observed.